2023
DOI: 10.1186/s12890-023-02522-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of Ureaplasma infection pattern and azithromycin treatment effect with bronchopulmonary dysplasia in Ureaplasma positive infants: a cohort study

Abstract: Background It is unclear whether Ureaplasma-associated pneumonia and azithromycin treatment affect the risk for bronchopulmonary dysplasia (BPD). Methods A retrospective cohort study was performed in very low birth weight (VLBW) infants who tested positive for Ureaplasma within 72 h after birth in a tertiary unit. Chest X-ray (CXR) and laboratory test were performed before and after azithromycin treatment. Multivariate logistic regression analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…Treatment could also be considered if there is also high clinical and radiographic suspicion of active infection. 223 Early Course: First Week of Life -Fluid Management and Nutritional Strategies Subgroup analysis of the multicenter Preterm Erythropoietin Neuroprotection Trial (PENUT) revealed that higher peak fluid balance (calculated by percentage change in weight from BW) was associated with increased risk for IMV on DOL 14 and in the combined outcome for BPD and mortality. 109 Every 10% increase in peak fluid balance was associated with 103% increased odds of receipt of IMV on DOL 14 (aOR: 2.03, 95% CI: 1.64-2.51).…”
Section: Early Course: First Week Of Life -Judicious Use Of Antimicro...mentioning
confidence: 99%
“…Treatment could also be considered if there is also high clinical and radiographic suspicion of active infection. 223 Early Course: First Week of Life -Fluid Management and Nutritional Strategies Subgroup analysis of the multicenter Preterm Erythropoietin Neuroprotection Trial (PENUT) revealed that higher peak fluid balance (calculated by percentage change in weight from BW) was associated with increased risk for IMV on DOL 14 and in the combined outcome for BPD and mortality. 109 Every 10% increase in peak fluid balance was associated with 103% increased odds of receipt of IMV on DOL 14 (aOR: 2.03, 95% CI: 1.64-2.51).…”
Section: Early Course: First Week Of Life -Judicious Use Of Antimicro...mentioning
confidence: 99%